2014
DOI: 10.2147/ijn.s56756
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the endometrium of rats, rabbits, and Macaca mulatta that received an implantation of copper/low-density polyethylene nanocomposite

Abstract: A copper/low-density polyethylene nanocomposite (nano-Cu/LDPE), a potential intrauterine device component material, has been developed from our research. A logical extension of our previous work, this study was conducted to investigate the expression of plasminogen activator inhibitor 1 (PAI-1), substance P (SP), and substance P receptor (SP-R) in the endometrium of Sprague Dawley rats, New Zealand White rabbits, and Macaca mulatta implanted with nano-Cu/LDPE composite. The influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Recently, Cu NP has shown great promise as an antibacterial material [4][5][6][7] and even been used as intrauterine contraceptive device (IUD). [8][9][10][11][12][13][14] Recently, a new type of nano-Cu IUD was invented by However, numerous studies have unequivocally indicated that exposure to Cu NPs can result in adverse effects in vivo and in vitro. [16][17][18][19][20] For instance, a previous study demonstrated that the exposure of mice to Cu NPs resulted in severe kidney, liver, and spleen impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cu NP has shown great promise as an antibacterial material [4][5][6][7] and even been used as intrauterine contraceptive device (IUD). [8][9][10][11][12][13][14] Recently, a new type of nano-Cu IUD was invented by However, numerous studies have unequivocally indicated that exposure to Cu NPs can result in adverse effects in vivo and in vitro. [16][17][18][19][20] For instance, a previous study demonstrated that the exposure of mice to Cu NPs resulted in severe kidney, liver, and spleen impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous in vivo studies demonstrated that exposure to 12.5 mg/kg/d Cu‐NPs for 14 days led to an obvious accumulation in the ovaries, resulting in ovarian injury, an imbalance in sex hormone levels, and ovarian cell apoptosis . In previous studies, our research team successfully applied Cu‐NPs to develop a novel copper/low‐density polyethylene nanocomposite material for intrauterine devices (IUDs) . Our experiments revealed that this material had a high contraceptive efficacy and reliable safety, with low rates of side effects.…”
Section: Introductionmentioning
confidence: 87%
“…The process used to prepare the nano-Cu/LDPE IUD was introduced in our previous work (Figure 3). 8 The nano-Cu/LDPE IUD comprises a pair of symmetrical transverse arms with a total length of 28 mm and a longitudinal stem with a total height of 30 mm. Both the transverse arms and the longitudinal stem have a diameter of 2.0 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, controlling the process of cupric ion release and thus preventing such a burst initially after insertion should be considered to maximize contraceptive efficacy and minimize adverse effects. 8 Recent decades have seen rapid advances in nanotechnology in many scientific fields ( Figure 2). The characteristics of nanomaterials have contributed to notable biomedical achievements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation